TRANSFORMASI BIROKRASI PELAYANAN PUBLIK DI ERA DIGITAL: STUDI FENOMENOLOGI DI SUB BAGIAN TATA USAHA BALAI VETERINER LAMPUNG - Muhammad Samsuri Efendi; M. Yusuf S. Barusman (Jurnal Riset Multidisiplin Edukasi, 2026)
The transformation of public service bureaucracy in the digital era has become an essential demand to improve the effectiveness, efficiency, transparency, and accountability of government performance. Digitalization not only changes the use of technology in administrative processes but also influences work patterns, organizational culture, and how public officials perceive public services. This study aims to analyze the experiences of civil servants in implementing digital-based public service bureaucratic transformation in the Administrative Subdivision of the Lampung Veterinary Center. The research employed a qualitative approach using a phenomenological method. Data were collected through in-depth interviews, observations, and documentation, while the data were analyzed using thematic analysis techniques. The findings show that the digitalization of administrative systems has improved work efficiency, accelerated service processes, enhanced data accuracy, and facilitated real-time document access and monitoring. However, the implementation of digital transformation still faces several challenges, including limited network infrastructure, inadequate supporting devices, and variations in digital competencies among civil servants. Therefore, the success of digital bureaucratic transformation is strongly influenced by human resource readiness, organizational work culture, and sustainable policy support.